Make a Decision to use AHP for the Selection of Materials and Designs for Minimizing Environmental Impacts by the POPE Lawn Mower Manufacturing - Abbas, Mohammed; M, Ashham; K, Salman; Almukhtar, M.; h .al tameemi, Zaid; kadhim sharaf, Hussein (International Journal of Engineering and Technology, 2018)
The POPE lawn mower has turned out to be a standout amongst householder machines. This is because of many individuals are utilizing yard trimmers consistently to cut the grass in their home, open parks or road borderlines to keep up an excellent domain. In any case, this item has some negative effects on nature, for example, gases outflows and production of strong or fluid waste. Likewise, this item has a few issues, for example, corrosion on the materials of a few sections, and a wasteful and short life expectancy. The effects on the environment related with POPE lawn mowers are an outcome of the materials and configuration utilized as a part of the assembling procedure. Besides, the motivation behind this paper is to portray, analyse the POPE lawn mower segments, and propose how it could enhance the choice of new materials and designs used during  the assembling procedure. The discoveries of this paper task will propose a few arrangements by utilizing the Analytic Hierarchy Process (AHP) to make a choice, which allows for a selection of new materials and designs for manufacturing the POPE lawn mower with less environmental impacts and greater efficiency. Finally , this study is encourage the organizations which fabricating the POPE lawn mower to enhance the lawn  mawer by choosing new design , materials and making changes to the energy consumption to make this item more proficient with less ecological effects Keywords: Pope lawn mower, environmental impacts ,AHP